2023
DOI: 10.4322/bds.2023.e3638
|View full text |Cite
|
Sign up to set email alerts
|

Wear of dental ceramics

Abstract: Based on the development of adhesive dentistry, minimally invasive restorations in ceramics are used as alternatives to restore a tooth. Dental ceramics are largely applied in the dentistry field mainly due to their esthetic and mechanical strength. One of the ceramic properties to be well known before its use is the wear resistance that should be compatible with the antagonist wear behavior to avoid unwanted performance. Therefore, several methods have been performed to assess the ceramic materials wear behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 121 publications
0
9
0
4
Order By: Relevance
“…Various factors, including composition, sintering conditions, and translucency, affect the final shade of zirconia restorations. While extensive research has been conducted on shade characterization for traditional zirconia, 29 30 more investigation is needed specifically for 3D-printed zirconia. The unique properties of 3D-printed zirconia, such as different printing parameters and postprocessing techniques, may introduce additional complexities in achieving precise shade matching.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, including composition, sintering conditions, and translucency, affect the final shade of zirconia restorations. While extensive research has been conducted on shade characterization for traditional zirconia, 29 30 more investigation is needed specifically for 3D-printed zirconia. The unique properties of 3D-printed zirconia, such as different printing parameters and postprocessing techniques, may introduce additional complexities in achieving precise shade matching.…”
Section: Discussionmentioning
confidence: 99%
“…Two-body-wear, three-body wear, and toothbrushing tests have been described in the literature among the most common in vitro methodologies to investigate wear in ceramic restorative materials [ 61 , 62 ]. The toothbrushing test is used for assessing the abrasion wear of ceramic materials and examining the wear of the glaze or extrinsically stained layers.…”
Section: Discussionmentioning
confidence: 99%
“…The three-body wear test replicates clinical conditions to simulate occlusal wear through the introduction of a third abrasive body between the ceramic surface and the opposing surface simulating food bolus. Studies on composite and amalgam samples revealed that gradual change in the distance between the opposing substrates and even minor alterations of the abrasive-film features and thickness at the contact areas result in significant changes in wear rates and wear-rate ranking of the materials [ 61 , 62 ]. Two-body wear tests are suitable for predicting the wear behavior of dental materials [ 44 ] through the simulation of non-masticatory tooth movements such as swallowing, empty mastication, parafunctions and dynamic occlusion movements [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…By choosing materials with lower surface roughness, the dentist and the dental technician can reduce the risk of bacterial plaque retention and improve the long-term success of the dental treatments [ 10 , 13 , 21 , 30 ]. Additionally, it can facilitate proper maintenance and cleaning of dental materials to prevent the buildup of bacterial plaque [ 25 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro fatigue tests, which involve applying cyclic loads to simulate the clinical conditions experienced by the restorative materials in the oral cavity, have been widely utilized [ 13 , 14 ]. These tests provide valuable insights into the probability of survival or failure of the ceramic restorations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%